Factors Causing Low the Scientific Ability of Indonesian Children: A Systematic Review - Sudarto, Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Factors Causing Low the Scientific Ability of Indonesian Children: A Systematic Review. The low scientific ability of Indonesian children was a serious issue that impacted the quality of human resources and national competitiveness in the global era. Objective: This study aimed to identify the main factors causing the low scientific ability of Indonesian children through a systematic literature review of 52 articles indexed in Sinta 1, Sinta 2, and the Scopus database. The thematic analysis grouped the causal factors into aspects of teacher quality and teaching practices, curriculum and assessment, laboratory facilities and infrastructure, basic literacy and numeracy of students, motivation and attitudes toward science, as well as socioeconomic factors. The study results showed that the low mastery of scientific concepts and process skills was caused by a combination of pedagogical challenges, curriculum policies that inadequately supported scientific learning, limited facilities, and uneven socioeconomic concerns. The study implied the necessity of educational reform integrating teacher training, curriculum renewal based on scientific literacy and experimentation, improved learning facilities, and empowerment of student motivation and understanding to sustainably enhance the scientific ability of Indonesian children.